STUDY OF CORONAVIRUS DISEASE 2019 (COVID-19) VACCINATION IN INDONESIA: A LITERATURE REVIEW - Theresia Lidia; Aris Widayati (Sanata Dharma University, 2021)
Research and development of the COVID-19 vaccine give hope to all people to stop the COVID-19 pandemic in the world. This literature review explores the safety and efficacy of the COVID-19 vaccine used in Indonesia and discusses Indonesia's current vaccination process. The primary databases for the reviewed articles were PubMed and Mendeley. Others are official websites, such as World Health Organization (WHO); COVID-19 and National Economic Recovery Committee in Indonesia (KPCPEN); the National Agency of Drug and Food Control (NA-DFC–in Bahasa Indonesia: BPOM) of the Republic of Indonesia; the US Food and Drug Administration (FDA), Clinical Trials.gov, COVID-19 vaccine Tracker, the Indonesian regulations, and guidelines regarding COVID-19. The inclusion criteria of the searched articles were those published from December 2019 to April 30, 2021, and those which discussed vaccines' types, efficacy, and safety. Acceptance of the COVID-19 vaccination is quite high (65%). Refusal was related to vaccine safety (30%); effectiveness (22%); distrust of vaccines (13%); fear of side effects (12%); and religious reasons (8%). The COVID-19 vaccines planned by the Indonesia Government have gone through clinical trials phases I to III. The Coronavac vaccine efficacy showed seroconversion that occurred was 92.4% to 97.4%, and no severe side effects have been reported. The ChAdOx1 nCoV-19 efficacy was 66.7% to 76.0%, and none of the tested participants was hospitalized, serious side effects were very small (0.9% to 1.1%). The mRNA-1273 efficacy was 94.1%, and its reactogenicity was mild to moderate. The BNT162b2 efficacy was ≥ 92%, and no severe or specific safety concerns have occurred. The efficacy of the BBIBPCorV vaccine has not been established. Ongoing phase I, II, and III clinical trials will provide more information on safety and immunogenicity for the BBIBP-CorV. Three of the six vaccines have obtained EUA from BPOM and approval from the Indonesian Ulema Council (MUI). A health promotion program about the safety, efficacy, and the 'halal' of the COVID-19 vaccine; acceleration and ensuring access to the COVID-19 vaccination program are urgent to end this pandemic immediately.